Sustainable aerogels derived from bio-based 2, 5-diformylfuran and depolymerization products of lignin. Issue 1 (1st January 2021) - Derflinger, Christoph; Kamm, Birgit; Paulik, Christian
ABSTRACT: 2, 5-diformylfuran (DFF) is a promising green platform chemical obtainable by selective oxidation of 5-(hydroxymethyl)furfural (HMF). In this work, high-purity DFF was synthesized from HMF and compared to formaldehyde (F) in terms of suitability for polymerization in aqueous solution with various phenolic model substances that may be obtainable by depolymerization of lignin. Resorcinol, catechol, and phloroglucinol formed stable hydrogels with DFF, which were converted to alcogels and subsequently dried by extraction with supercritical carbon dioxide. Thermogravimetric analysis and scanning electron microscopy of the resulting aerogels showed no significant differences between DFF and F gels. The high porosity of the aerogels was confirmed by liquid nitrogen BET surface measurement; the specific surface areas measured varied significantly, ranging from 20 to 700 m 2 g −1 . Graphical Abstract: uf0001